(untitled) (Research, Society and Development, 2021)
This article presents a systematized reflection and discussion around three guiding axes: the first discusses the vulnerability of women enhanced by the COVID-19 pandemic; in the second, it reflects on public policies for women’s health in Brazil and COVID-19’s coping strategies with the objective of maintaining women’s health and mitigating the effects of the pandemic; and the third reflects on the nursing care for women in vulnerable situations in the face of the pandemic. The conclusion is that the COVID-19 pandemic has had a major impact on vulnerable women with countless consequences that add to the inequities and the many vulnerabilities that already exist. The post-pandemic scenario will require collective efforts to protect and guarantee the health of women in vulnerable situations, which are intertwined with the articulation of public policies with the specific procedures of health organizations; the participation of women in the formulation of these policies and nursing care.